(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
The African Court on Human and Peoples’ Rights (African Court) advisory opinion in Pan African Lawyers Union on the compatibility of vagrancy laws with the African Charter on Human and Peoples’ Rights and other human rights instruments in Africa (PALU opinion) 1/2018 recommends that states amend or repeal vagrancy offences that criminalise the life-sustaining activities of many persons targeted by these laws. The Court’s main opinion is that states’ national laws and by-laws containing vagrancy offences are vague, overly broad and ambiguous, conferring broad discretion on the police for their enforcement and targets people in terms of their status, not their conduct. These laws violate articles 2, 3, 5, 6, 7, 12 and 18 of the African Charter on Human and Peoples’ Rights; articles 3 and 17 of the African Charter on the Rights and Welfare of the Child; and article 24 of the Protocol to the African Charter on the Rights of Women in Africa. The main opinion insufficiently addresses the colonial root of vagrancy. A separate concurring opinion elaborates on the margin of appreciation and good faith principle that allow states to formulate contextspecific answers to amend and repeal vagrancy offences. This article identifies the impact of the COVID-19 pandemic on petty offences enforcement and draws lessons from litigation such as Gwanda v The State and interventions from national human rights institutions such as the South African Human Rights Commission; as well as guidance from the African Commission on Human and Peoples’ Rights Principles on Decriminalisation of Petty Offences in Africa (2017). It is argued that specific institutional and non-material interventions are needed to bring the systemic change required, in tandem with the banning of vagrancy offences, for cities that promote inclusion and sustainable development for all.